The Mechanism of Centriole Inactivation in Starfish Oocytes - Pinto, Joana Borrego (2018)
The centrosome is the major organizing center in a cell, composed by two centrioles, one mother and one daughter, and surrounded by a pericentriolar material, which nucleates microtubules. Centriole duplication and segregation is tightly coupled to cell cycle, which guarantees that centriole number is maintained over generations. During the somatic cell cycle, a pair of centrioles duplicates, after which each daughter cell receives a pair, forming a closed cycle. However, during fertilization, if both cells were to contribute with their pair of centrioles, gamete fusion would result in the double of the normal centriole number.(...)